The folding and misfolding mechanisms of multidomain proteins - Yanfang Lu; Bin Zhu; Qianqian Li; Jiang Du; Tao Chen (Elsevier, 2022)
The reliable folding of proteins is essential for their biological activities, while misfolding may lead to severe diseases, such as Alzheimer's disease. However, our current knowledge of protein folding arises mainly from studies on small, single-domain proteins rather than multidomain proteins, although the latter make up most of proteins in the cell. Due to complex topological structures and potential interdomain interactions, the refolding of many multidomain proteins often passes through long-lived partially folded intermediates and exhibits complex kinetics. Here, we survey recent progress in understanding the folding and misfolding of multidomain proteins in vitro, with particular reference to theoretical aspects, and briefly summarize the researches on how ribosome regulates folding kinetics of nascent chains during translation in vivo, such as the environmental effects of the ribosome, translation rate effects, and self-interactions effects of polypeptide chain. In addition to these important advances, many questions are still waiting for answer, including: Can a purely structure-based model capture the complex folding kinetics of some multidomain proteins caused by the significant energetic frustration? Is the energy landscape of cotranslational folding still perfectly funnel-like? Are the observed principles that ribosome promotes the proper folding of proteins universal? To what extent does cotranslational folding affect nonnative interactions? Collectively, to address these issues, further innovation and improvement on both experimental techniques and the computational models are in great demand.